Immunonutrition in cancer patients: integrative review (Research, Society and Development, 2020)
Cancer is a denomination that covers more than 100 types of disease and its main feature is the accelerated growth of abnormal cells that affects the other tissues of the body. Its onset may come from several causes, which may act simultaneously or individually to initiate the process of carcinogenesis. The aim of this study is to demonstrate the benefits of immunomodulators in cancer patients. It is an integrative review with a qualitative approach. To perform this research, a bibliographic survey was made to select studies in the online databases: Virtual Health Library (VHL), Pubmed, Science direct. Regarding the results, the selected studies involved the participation of 15 to 776 patients. Most of these studies were performed using enteral immunonutrition. Participant ages ranged from 18 to 75 years. Studies have shown that immunonutrition had a significant effect on patients with cancer, as it had a positive impact on reducing postoperative complications such as infectious and inflammatory processes, increased serum albumin, reduced length of hospital stay and immune system improvement. The results showed that the immunomodulatory diets were effective in the pre and postoperative period, reducing the possible complications, becoming a safe alternative to optimize the results after the surgical procedures. The articles underscored the importance of knowing when to start nutritional support with supplementation before surgery, as this contributes to good results after treatment.